Exploring cationic amylose inclusion complexes as a pioneering carrier for aroma molecules; fabrication, and characterization - Zohreh Mokhtari; Seid Mahdi Jafari (Carbohydrate Polymer Technologies and Applications)
Amylose complexes are considered excellent carriers for flavor compounds (FCs), leading to their controlled release. Nevertheless, the utilization of native amylose for the creation of inclusion complexes (ICs) is constrained by its pronounced propensity for retrogradation (re-crystallization) and its limited water solubility. Therefore, chemical modification of amylose stands as an innovative approach to generate soluble ICs. This study focused on generating and evaluating ICs composed of cationic amylose sourced from sago and corn, which then loaded with FCs (menthol, thymol, and eugenol). The characteristics of ICs with FCs were characterized in terms of including X-ray diffraction (XRD), Complex Index, Fourier transform infrared/Raman spectroscopy, and scanning electron/atomic force microscopy. The XRD and the complex index findings suggested that cationizing the anhydroglucose units of amylose was accomplished without disrupting its helical structure, while also showing a promising ability to create ICs. Notably, sago amylose exhibited a significantly higher complex index compared to corn amylose (p < 0.05). Morphological analysis of the cationized amylose-flavor ICs revealed the presence of spherical and lamellar crystalline structures, suggesting a well-organized assembly resulting from ICs. Also, due to its high hydrophobicity and low vapor pressure, menthol in the presence of ethanol was able to form more ICs with amylose compared to thymol and eugenol. Finally, the study highlighted the unique properties of sago amylose, including its high retrogradation tendency, which was further enhanced by cationization. These findings underscore the utility of cationized amylose, particularly from sago, as an advanced material for encapsulating hydrophobic compounds.